Major burden of severe anemia from non-falciparum malaria species in Southern Papua: a hospital-based surveillance study. - Douglas, N; Lampah, D; Kenangalem, E; Simpson, J; Poespoprodjo, JR; Sugiarto, P; Anstey, N; Price, R (2013)
BACKGROUND: The burden of anemia attributable to non-falciparum malarias in regions with Plasmodium co-endemicity is poorly documented. We compared the hematological profile of patients with and without malaria in southern Papua, Indonesia. METHODS AND FINDINGS: Clinical and laboratory data were linked for all patients presenting to a referral hospital between April 2004 and December 2012. Data were available on patient demographics, malaria diagnosis, hemoglobin concentration, and clinical outcome, but other potential causes of anemia could not be identified reliably. Of 922,120 patient episodes (837,989 as outpatients and 84,131 as inpatients), a total of 219,845 (23.8%) were associated with a hemoglobin measurement, of whom 67,696 (30.8%) had malaria. Patients with P. malariae infection had the lowest hemoglobin concentration (n = 1,608, mean = 8.93 [95% CI 8.81-9.06]), followed by those with mixed species infections (n = 8,645, mean = 9.22 [95% CI 9.16-9.28]), P. falciparum (n = 37,554, mean = 9.47 [95% CI 9.44-9.50]), and P. vivax (n = 19,858, mean = 9.53 [95% CI 9.49-9.57]); p-value for all comparisons <0.001. Severe anemia (hemoglobin <5 g/dl) was present in 8,151 (3.7%) patients. Compared to patients without malaria, those with mixed Plasmodium infection were at greatest risk of severe anemia (adjusted odds ratio [AOR] 3.25 [95% CI 2.99-3.54]); AORs for severe anaemia associated with P. falciparum, P. vivax, and P. malariae were 2.11 (95% CI 2.00-2.23), 1.87 (95% CI 1.74-2.01), and 2.18 (95% CI 1.76-2.67), respectively, p<0.001. Overall, 12.2% (95% CI 11.2%-13.3%) of severe anemia was attributable to non-falciparum infections compared with 15.1% (95% CI 13.9%-16.3%) for P. falciparum monoinfections. Patients with severe anemia had an increased risk of death (AOR = 5.80 [95% CI 5.17-6.50]; p<0.001). Not all patients had a hemoglobin measurement, thus limitations of the study include the potential for selection bias, and possible residual confounding in multivariable analyses. CONCLUSIONS: In Papua P. vivax is the dominant cause of severe anemia in early infancy, mixed P. vivax/P. falciparum infections are associated with a greater hematological impairment than either species alone, and in adulthood P. malariae, although rare, is associated with the lowest hemoglobin concentration. These findings highlight the public health importance of integrated genus-wide malaria control strategies in areas of Plasmodium co-endemicity.